The women barangay health workers of Miagao, Iloilo conditions and contributions - Prieto-Carolino, Alice; Firmase, Josephine T. (Danyag :the UPV journal of humanities and social sciences, 2010)
"The Women Barangay Health Workers of Miagao are the front liners in the delivery of primary care but they remain as the most undervalued human resources in the health sector and their work is unrecognized. Alongside their community managing activities, they also undertake productive and reproductive activities that are promotive of their families' and communities' well-being. Despite the challenges they face in the performance of their duties as BHWs, they continue to volunteer duties as BHWs, they continue to volunteer since they know the significant role they play in the promotion of health and they derive a great sense of fulfillment in helping other people. It is thus recommended that a concerted effort of the local and national government, private institutions and individuals, non-government, private institutions and individuals, non-government organizations, the academe, and the BHWs themselves should be geared towards the promotion of their well being as women and as barangay health workers."